Mediasi Diversi dalam Sistem Peradilan Pidana Anak di Balai Pemasyarakatan Kelas I Manado - Stefy Meify Andih; Devy K.G Sondakh; Natalia L. Lengkong (Journal on Education, 2023)
Children are the next generation of the nation, therefore it is the obligation of all parties, especially the state, to prepare and protect their future so that regeneration can run well. When a child commits a crime, child delinquency can no longer be seen as ordinary delinquency. Many children commit acts that are classified as criminal acts, such as: stealing, carrying sharp weapons, getting into fights, being involved in drug use, and so on. This requires serious attention from both the government, parents and society. This research method is survey research with techniques using library research material collection techniques. Besides that, the author also conducted field research by conducting direct research through interviews with officers at the Manado Class I Correctional Hall, the police, the prosecutors, and the judges in the North Sulawesi Region. The results of this study show how the process of diversion mediation at the level of the police, the prosecutors, and the judges. In addition, it discusses the role of the social counselor at the Manado Class I Correctional Hall as a mediator in the implementation of diversion mediation in the North Sulawesi region in accordance with Law of The Republic of Indonesia Number 11 of 2012 on the Juvenile Criminal Justice System.